Non Performing Assets in Public Sector Banks: A Cause Analysis - Naveenan, R.V.; Kumar, B. Ravi; Lakshmi, B. Vijaya (American Finance & Banking Review, 2018)
Lending Funds is considered as the primary function of primary function which provides financial support to various sectors such as agriculture, industry, personal loans etc., but in recent times the banks as taken a cautious stand in lending. The main reason for such an initiative is the mounting issues of non-performing assets (NPAs).A loan asset is considered as non-performing asset when it ceases to generate income for the bank. From 31st March, 2004 NPA was defined as a credit facility in respect of which the interest or installation of principal has remained past due for a specified period of time which was four quarters. NPA in public sector banks is increasing year after year and thus this is becoming a debatable topic. So considering this anglete paper is undertaken to analyze the reasons for advances becoming NPA in Public sector banks and intends to give suitable suggestions to overcome NPA.